Anonim ortaklıkların kuruluşu - Biton, Erika (My University, 2006)
ANONİM ORTAKLIKLARIN KURULUŞU Ortaçağda ortaya çıkan ve ticari amaç taşıyan tüzel kişiler 16.17. yüzyılda gelişerek modern anlamda anonim ortaklıkların ilk örneklerini ortaya çıkarmıştır. Yaşanan gelişmeler sonucunda ortaya çıkan bu ortaklıklar kişiliği, şahsi varlığı önem arz etmeyen ve kar amacı ile hareket eden pay sahibi varlığına ve sermaye birikimini sağlayan ortaklık biçimine dayanır. Bu ortaklıkların kuruluşlarını incelediğimiz tezimizde ilk bölümde genel açıklamaları, işlem ve aşamaları, ikinci bölümde kuruluşta yapılan işlemleri, ortaklığın kurulamaması, kuruluştan doğan sorumluluk, 3. bölümde genel kuruluş hükümlerinden farklı ortaklıkları, dördüncü bölümde ise Avrupa Birliği mevzuatı, üye ülke uygulamaları ve Avrupa Şirketi ele alınmıştır. Ayrıca ilgili bölümlerde Türk Ticaret Kanunu Tasarısı ele alınmış mevcut durumdan ayrıldığı noktalar belirtilmiştir. SETTELMENT OF ASSOCIATIONS Legal entities with a commercial aim have been known from the middle ages, and they have been developed in 16th and 17th centuries and became the first examples of the modern associations. With developments associations became an entity which the founder’s individuality has no importance, and the founders have a motive of gaining profits. The corporation is based on the capital deposition. We have reviewed the settlement of those corporations. In the first chapter we have explained the issue in general terms, and mentioned the operations, and transactions. In the second chapter we have reviewed the transactions, non settlement of the corporation, the liability of the settlement, in the third chapter the differences of the special associations from the general terms of settlement, and in the fourth chapter we have mentioned the European Union’s current law, the member state practices and the Societé Anonyme. Moreover we have mentioned the Draft Turkish Commercial Code, and the differences from the present code.
Keywords: Anonim Şirketler_Hukuk; Özel Hukuk